Chapter 2 School food approaches in Peru, Colombia and Ecuador Intentions, illusions and uncertainties - Torres, Irene (Taylor & Francis, 2022)
The purpose of this chapter is to compare approaches to school food in Peru, Ecuador and Colombia from an educational perspective, taking into consideration national policy documents, plans and programs. The focus is on the purported social justice aims of school food initiatives, including their intent to improve learning and educational achievement or the social protection of marginalized communities. The authors explore the versions of health and education that are put forth in official texts, and how these versions are supported by equity-oriented mechanisms that are advanced or affirmed in the same texts. Using thematic analysis, the most salient characteristics of food plans and programs in the three countries are synthesized, and recommendations are formulated considering that school food can be aimed at improving health and wellbeing, but not necessarily only due to its nutritional contents. The messages that are woven around food in educational settings may be equally or more important. Lastly, a brief discussion of school food policies in the context of the COVID-19 pandemic response is included.